2011
DOI: 10.3345/kjp.2011.54.12.501
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of air pollution and the prevalence of allergy-related diseases in Incheon and Jeju City

Abstract: PurposeA high level of air pollutants can increase the number of patients with allergy-related diseases such as asthma and allergic rhinitis (AR). To analyze the association between air pollution and allergic disease, we investigated 2 areas in Korea: Incheon, an industrial area, and Jeju, a non-industrialized area.MethodsSecond grade students at elementary schools (11 schools in Incheon and 45 schools in Jeju) were examined in a cross-sectional study. A questionnaire was used and a skin prick test was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…The prevalence of allergic rhinitis is higher in populations that reside in more polluted areas or near roads with heavier traffic than in populations with less pollutant exposure. 16 , 51 While air pollution is considered to be a respiratory environmental factor because it is primarily inhaled into respiratory systems, it is also associated with eczema and skin disease. 52 Indeed, a recent study has shown that the amount of air pollutants such as NO, toluene, and VOCs correlate with eczema symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of allergic rhinitis is higher in populations that reside in more polluted areas or near roads with heavier traffic than in populations with less pollutant exposure. 16 , 51 While air pollution is considered to be a respiratory environmental factor because it is primarily inhaled into respiratory systems, it is also associated with eczema and skin disease. 52 Indeed, a recent study has shown that the amount of air pollutants such as NO, toluene, and VOCs correlate with eczema symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The relative risks of emergency outpatient hospital visits are all positively and significantly associated with interquartile increases for selected lags for all air pollutants in Korea [41]. Similarly, a comparative study found that the prevalence rates of asthma symptoms are significantly higher in Incheon, Korea, which has significantly higher levels of outdoor CO and PM than Jeju, Korea [42]. However, Kim et al [43] found no such association between air pollutant levels and the relative risk of emergency room visits.…”
Section: Introductionmentioning
confidence: 99%
“…In the rapidly developing society with industrialization and urbanization, air pollution and other environmental changes have caused a significant increase in AR prevalence and symptom severity. 1 Particulate matter 2.5 (PM2.5) obviously aggravates AR patients’ condition and is an important cause of AR incidence; it promotes the progress of AR nasal mucosa inflammation. 2 Therefore, the impact and serious harm by air pollutants such as PM2.5 should be emphasized during the prevention and treatment of AR.…”
mentioning
confidence: 99%